PERSONAL HYGIENE AND DERMATITIS INCIDENCE IN RESIDENTS OF RIANG NAIBONAT CHILDREN’S SOCIAL ASSOCIATION - Djami Hae, Mony Veronika; Umburoga, Anderias; Marni, Marni; Purimahua, Sintha Lisa (HEARTY, 2025)
Skin disease is one of the health problems that are still often found in orphanages. Factors such as environmental cleanliness and personal hygiene habits play an important role in preventing skin diseases. The purpose of this study was to determine environmental sanitation and personal hygiene with the incidence of skin diseases in adolescents at the UPTD of the Riang Naibonat Children’s Social Welfare Institution. This type of research is descriptive and was conducted by survey. This study was conducted at the UPTD of the Riang Naibonat Children’s Social Welfare Institution with a sample of 64 beneficiaries. The data analysis used was univariate analysis which only looked at the frequency distribution of each variable studied. The study stated that poor bed hygiene was 38 people (59.4%), poor towel hygiene was 34 people (53.1%), poor clothing hygiene was 19 people (29.7%), poor skin and hair hygiene was 5 people (7.8%) and poor hand and nail hygiene was 37 people (57.8%). Children living in orphanages should be accustomed to implementing a clean and healthy lifestyle in their daily activities. To support this, the role of orphanages and health workers is greatly needed, especially in providing easy-to-understand education.